A Steady‐State Head‐to‐Head Pharmacokinetic Comparison of All FK‐506 (Tacrolimus) Formulations (ASTCOFF): An Open‐Label, Prospective, Randomized, Two‐Arm, Three‐Period Crossover Study - Tremblay, S.; Nigro, V.; Weinberg, J.; Woodle, E. S.; Alloway, R. R. (American journal of transplantation, 2017)
This two‐sequence, three‐period crossover study is the first pharmacokinetic (PK) study to compare all three innovator formulations of tacrolimus (twice‐daily immediate‐release tacrolimus capsules [IR‐Tac]; once‐daily extended‐release tacrolimus capsules [ER‐Tac]; novel once‐daily tacrolimus tablets [LCPT]). Stable renal transplant patients were dosed with each drug for 7 days, and blood samples were obtained over 24 h. Thirty subjects were included in the PK analysis set. A conversion factor of 1:1:0.80 for IR‐Tac:ER‐Tac:LCPT was used; no dose adjustments were permitted during the study. The median (interquartile range) total daily dose was 6.0 (4.0–8.0) mg for IR‐Tac and ER‐Tac and 4.8 (3.3–6.3) for LCPT. Significantly higher exposure on a per milligram basis, lower intraday fluctuation and prolonged time (Tmax) to peak concentration (Cmax) were found for LCPT versus IR‐Tac or ER‐Tac. ER‐Tac showed no differences versus IR‐Tac in exposure, Cmax, Tmax or fluctuation. The observed exposure of IR‐Tac was used to normalize exposure for LCPT and ER‐Tac, resulting in the following recommended total daily dose conversion rates: IR‐Tac:ER‐Tac, +8%; IR‐Tac:LCPT, −30%; ER‐Tac:LCPT, −36%. After exposure normalization, Cmax was ~17% lower for LCPT than for IR‐Tac or ER‐Tac; Cmin was ~6% lower for LCPT compared with IR‐Tac and 3% higher compared with ER‐Tac. This study evaluates the pharmacokinetic profile of three tacrolimus formulations and shows significant differences, highlighting the higher per mg exposure and a lower peak and delayed peak of extended‐release tacrolimus tablets when compared to the two other capsule formulations.